\(η\)-Einstein \((k,μ )\)-space Forms - Shashidhar, Savithri; Nagaraja, H. G. (Journal of Informatics and Mathematical Sciences, 2015)
In the paper we obtain the scalar curvatures of a \((k,μ)\)-space form under \(h\)-projective, \(φ\)-projective semi symmetric and \(h\)-Weyl and \(φ\)-Weyl semisymmetry conditions.